Case Report: Ovarian pregnancy, a rare but lethal condition: An analysis of 112 cases - Shao, Mengyuan; Wang, Xinyi; Zhou, Xin (Frontiers in Surgery, 2023)
Study Objective: To explore how to improve the treatment, and prognosis of ovarian pregnancy (OP). Patients: A total of 111 OP patients, one of the patients suffered from OP twice. Results: In this study, 112 OP cases confirmed by postoperative pathology were retrospectively analyzed. Common risk factors for OP were previous abdominal surgery (39.29%) and intrauterine device use (18.75%). We modified the ultrasonic classification into four types: gestational sac type, hematoma type I, hematoma type II, and intraperitoneal hemorrhage type. Among these four types, the proportion of patients who underwent emergency surgery as initial treatment after admission was 68.75%, 10.00%, 92.00%, and 81.36%, respectively. The treatment for hematoma type I patients were often delayed. The rate of OP rupture was 86.61%. All patients receiving methotrexate therapy failed. All these 112 cases underwent surgery treatment finally. The surgical procedures were removal of gestational tissues and ovarian repair using laparoscopy or laparotomy. No significant differences were observed in the operation time or intraoperative blood loss between laparoscopy and laparotomy. Laparoscopy showed less influence on patients regarding length of hospital stay and postoperative fever than laparotomy. Further, 49 patients who desired fertility were followed up over 3 years. Among them, 24 (48.98%) experienced spontaneous intrauterine pregnancy. Conclusion: Among the four modified ultrasonic classifications, hematoma type I was associated with more delays in surgical time. Laparoscopic surgery was a better choice for OP treatment. The reproductive prognosis of OP patients was promising.